Direct Observation of the Binding Mode of the Phosphonate Anchor to Nanosized Polyoxotitanate Clusters. Issue 49 (25th October 2013) - Chen, Yang; Trzop, Elzbieta; Sokolow, Jesse D.; Coppens, Philip
Abstract The structures of three newly synthesized phosphonate‐substituted polyoxotitanates are reported. The Ti/O core of [Ti4O(OEt)12(PhenylPO3)] (1) is the building block for two larger phosphonate‐substituted nanoclusters, [Ti25O26(OEt)36(PhenylPO3)6] (2) and [Ti26O26(OEt)39(PhenylPO3)6]Br (3). All compounds exhibit a not previously recognized triply bridging binding mode of the phosphonate anchor with short connecting TiO bonds, the average of which is 2.010(7) Å. Comparison with previously reported work suggests that the binding mode of the phosphonate anchor is strongly dependent on the structure of the underlying substrate.